Comparative analysis of innovation performance of European Union countries : Komparativna analiza inovacijskog učinka zemalja Europske unije - Novak, Ivan, ekonomist (Array, 2020)
This paper aims to examine the innovation performance of 28 European Union countries. Hypothesis of the paper states there is a significant difference of innovation performance between the old and the new EU members. Furthermore, the role of SMEs regarding innovation capacity may not be the same across EU. Using K-means clustering results indicated Germany, Ireland, France, Luxemburg and Austria as the most innovative countries and Bulgaria, Estonia, Latvia, Hungary, Poland and Slovakia as the least innovative countries. Czech Republic, Croatia, Cyprus, Denmark, Finland, Greece, Italy, Lithuania, Malta, Netherlands, Portugal, Slovenia, Sweden, United Kingdom and Spain were found to have a medium level of innovation performance. Furthermore, United Kingdom surpassed the average innovation level of the cluster for the small sized enterprises. Croatia was below the average level of the cluster regardless of the size of the enterprise. Romania was the outlier with the least innovation. In order to facilitate more innovation these findings may be valuable in creating more country specific recommendations for entrepreneurial policy.